Investors Return: Do Mutual Funds Cashflows Really Matter? - Erick, Mwambuli; Annabahati, Gwacha (Business Management and Strategy, 2023)
The study assessed mutual funds’ cash flows on investors’ returns in Tanzania. The study was guided by two predicting variables: economic condition (EC) and fund growth (FG). The predictor variables were tested on investors’ return (IR) as the dependent variable. The study employed a quantitative approach using secondary data generated through panel form in the series of 8 years from 2014 to 2021. The study collected facts with regard to the selected and tested variables from all five schemes in the mutual funds. The data were analysed by E-views 13 and STATA 15 for statistical assumptions tests and the inferential analysis towards relationship testing between study variables. The study findings revealed that both economic condition and fund growth had been found positive with a significant effect on investment return (IR) with p<0.05. The results imply that economic condition and fund growth influence the investment return through Tanzania’s mutual fund. Therefore, this study recommends that the government of Tanzania through its agencies, Capital Market Securities Authority (CMSA) and Bank of Tanzania (BOT), to invest more in growing the economy. This assures favourable economic conditions that will attract cashflows to mutual funds and assure fund growth and investors returns.